Stem canker caused by Phomopsis spp. Induces changes in polyamine levels and chlorophyll fluorescence parameters in pecan leaves - Mantz, Guillermo Martin; Rossi, Franco Rubén; Viretto, Pablo Esteban; Noelting, María Cristina; Maiale, Santiago Javier (Elsevier, 2021)
Pecan plants are attacked by the fungus Phomopsis spp. that causes stem canker, a serious and emerging disease in commercial orchards. Stem canker, which has been reported in several countries, negatively affects tree canopy health, eventually leading to production losses. The purpose of this study was to inquire into the physiology of pecan plants under stem canker attack by Phomopsis spp. To this end, pecan plants were inoculated with an isolate of Phomopsis spp. and several parameters, such as polyamines, proline, sugars, starch, chlorophyll fluorescence and canopy temperature were analysed. Under artificial inoculation, a high disease incidence was observed with symptoms similar to those in plants showing stem canker under field conditions. Furthermore, the infected stem showed dead tissue with brown necrotic discolouration in the xylem tissue. The free polyamines putrescine, spermidine, and spermine were detected and their levels decreased as leaves aged in the infected plants with respect to the controls. Chlorophyll fluorescence parameters, such as Sm, ψEO, and QbRC decreased under plant infection and therefore the K-band increased. Canopy temperature and proline content increased in the infected plants with respect to the controls while sugar content decreased. These data suggest that stem canker caused by Phomopsis spp. induces physiological changes that are similar to those observed in plants under drought stress. To our knowledge, this is the first study that documents the physiological and biochemical effects derived from pecan-Phomopsis interaction.